2003
DOI: 10.1046/j.0266-4909.2002.00007.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of web‐based collaborative learning: factors beyond technology

Abstract: Web-based collaborative learning has a large potential for knowledge acquisition. However, it has different characteristics compared with conventional learning scenarios; especially with respect to the social communication situation, message exchange, cognitive load and participation of the learners. To cope with possible problems resulting from these characteristics suitable instructional means have to be considered, like collaborative learning methods, on-line moderation, appropriate learning tasks or comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
11

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 27 publications
(29 reference statements)
1
58
0
11
Order By: Relevance
“…However, simply placing students into groups or creating group-based assessment tasks will not necessarily result in students developing these skills (Hron & Friedrich, 2003). In order to ensure students develop these skills, it is necessary to follow approaches specifically developed for these purposes (E. G. Cohen, 1994;Slavin, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…However, simply placing students into groups or creating group-based assessment tasks will not necessarily result in students developing these skills (Hron & Friedrich, 2003). In order to ensure students develop these skills, it is necessary to follow approaches specifically developed for these purposes (E. G. Cohen, 1994;Slavin, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, research findings have indicated that the preferable learning task should be project-like, problemand practically-oriented and require learners to take different points of view in order to foster their collaboration (Hron and Friedrich 2003). Additionally, the complexity of the learning task has been argued as an important factor in determining the effectiveness of collaborative learning (Kirschner, Paas and Kirschner 2009).…”
Section: Hinders and Enablers Of Collaborative Learningmentioning
confidence: 99%
“…The learning task of developing a business plan was project-like, problem-and practically-oriented and required learners to take different point of views (Hron and Friedrich 2003). The implementation of the task also included distance-learning (possibly at home) and asynchronous interaction, which require initiative and organization skills.…”
Section: A General Overviewmentioning
confidence: 99%
“…Digalo has been conceived to aim and facilitate learning through and learning about argumentation. Like other tools meant to support argumentative learning (Hron and Friedrich 2003), Digalo provides graphical and visual descriptions of arguments that can serve as external references for collective learning or problem solving.…”
Section: The Role Of Ict Tools In Argumentative Learningmentioning
confidence: 99%